Not Every Dyspepsia Is Related to Helicobacter pylori-A Case of Esophageal Inlet Patch in a Female Teenager - Lorena Elena Meliț; Andreea Ligia Dincă; Reka Borka Balas; Simona Mocanu; Cristina Oana Mărginean (MDPI AG, 2023)
Helicobacter pylori infection is one of the main causes of dyspepsia, but it is not the only cause. Esophageal inlet patches are areas of heterotopic gastric mucosa within the esophagus and are commonly located in the cervical part of the esophagus. We report the case of a 16-year-old female, previously known to display symptoms of anxiety, who was admitted to our clinic for dyspeptic symptoms lasting for approximately 1 month in spite of the treatment with proton pump inhibitors. The clinical exam revealed only abdominal tenderness in the epigastric area, while routine laboratory tests showed no abnormalities. The upper digestive endoscopy revealed a well-circumscribed salmon-pink-colored oval lesion of approximately 10 mm in the cervical esophagus, along with hyperemia of the gastric mucosa and biliary reflux. The histopathological exam established the diagnosis of esophageal inlet patch with heterotopic antral-type gastric mucosa and also revealed regenerative changes within the gastric mucosa. We continued to treat the patient with proton pump inhibitors, as well as ursodeoxycholic acid, with favorable evolution. Although rare or underdiagnosed, esophageal inlet patches should never be underestimated and all gastroenterologists should be aware of their presence when performing an upper digestive examination in a patient with dyspeptic symptoms.